Synthesis, Characterization, And Antiproliferative Studies Of Isoxazole Clubbed 1-Carbothioamido-4,5-Dihydro-1H-Pyrazoles (Journal of Pharmaceutical Negative Results, 2023)
Cancer remains a global problem despite the availability of drugs due to this issues like multi-drug resistance and toxicities. As a result, there is a pressing need for new anticancer medicines to be developed. In the present investigation, we designed and synthesized a series of Isoxazole clubbed 1-carbothioamido-4,5-dihydro-1H-pyrazoles (16-30) in considerable yields. Further, these compounds were purified by recrystallization and characterized by spectral techniques-Mass, FT-IR, and 1H NMR and then evaluated for their antiproliferative activity against prostate cancer DU-145 cell line. Among the tested compounds, The dihydro pyrazole-1-carbothioamides 28 and 29 showed the highest activity with IC50 value 1 µg/mL and the activity of these two compounds was four-fold more than that of the standard, Docetaxel. In addition, the less selectivity of these compounds against normal human liver cells suggests the significance of these compounds in the further discovery and development of novel anticancer drugs.